Estimation and Fitting Rainfall Pattern Distribution in Ghana using the Expectation-Maximization Algorithm with some Probability Models - Tuoyintir, Alexis (2017)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology In partial fulfillment of the requirement for the Degree of M.Phil Mathematical Statistics.